Metal Nanoparticles as Sustainable Tools for C–N Bond Formation via C–H Activation - Federica Valentini; Oriana Piermatti; Luigi Vaccaro (Molecules, 2021)
The design of highly active metal nanoparticles to be employed as efficient heterogeneous catalysts is a key tool for the construction of complex organic molecules and the minimization of their environmental costs. The formation of novel C–N bonds via C–H activation is an effective atom-economical strategy to access high value materials in pharmaceuticals, polymers, and natural product production. In this contribution, the literature of the last ten years on the use of metal nanoparticles in the processes involving direct C–N bond formation will be discussed. Where possible, a discussion on the role and influence of the support used for the immobilization and/or the metal chosen is reported. Particular attention was given to the description of the experiments performed to elucidate the active mechanism.